2012
DOI: 10.1161/circep.111.965095
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of the Coronary Vasculature in the Mechanisms of Defibrillation

Abstract: Background The direct role of coronary vessels in defibrillation, although hypothesized to be important, remains to be elucidated. We investigate how vessel-induced virtual-electrode polarizations assist reentry termination. Methods and Results A highly anatomically-detailed rabbit ventricular slice bidomain computer model was constructed from 25μm MR data, faithfully representing both structural and electrical properties of blood vessels. For comparison, an equivalent simplified model with intramural caviti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 23 publications
(53 reference statements)
1
29
1
Order By: Relevance
“…The investigators found that applied shock resulted in the formation of VEPs at the boundaries between blood vessels and myocardium. The VEPs elicited the formation of wavefronts that propagated through excitable gaps and led to successful defibrillation (Bishop et al, 2012). …”
Section: Termination Of Ventricular Arrhythmiamentioning
confidence: 99%
“…The investigators found that applied shock resulted in the formation of VEPs at the boundaries between blood vessels and myocardium. The VEPs elicited the formation of wavefronts that propagated through excitable gaps and led to successful defibrillation (Bishop et al, 2012). …”
Section: Termination Of Ventricular Arrhythmiamentioning
confidence: 99%
“…Application of similar techniques, suitably adapted for specific optical mapping setups, will allow the simulation of optical signals over the latest computational anatomical models, intramural cavities and all. An interesting first line of application of such models will be during defibrillation shocks due to the recent suggestion of the importance of 'virtual-electrode' formation around large subepicardial vessels (Bishop et al 2012;Luther et al 2012). It is thought that the interaction of photon scattering Fig.…”
Section: Modelling Approaches For Use In Conjunction With High-resolumentioning
confidence: 99%
“…For example, Bishop et al applied shocks to a very high-resolution (∼ 25 μm voxel size) image-based rabbit ventricular model; VEPs formed at the boundaries between blood vessels and myocardium [19], which gave rise to secondary sources that eliminated excitable gaps and led to successful defibrillation [23]. Simulations have also contributed to understanding of the process of defibrillation in hearts with myocardial ischemia and infarction [96,105,106], uncovering the role of electrophysiological and structural remodeling in the failure or success of the shock.…”
Section: Simulation Of Cardiac Arrhythmia Terminationmentioning
confidence: 99%
“…Simulations that require application of the bidomain formulation (e.g., defibrillation studies [23,44,96,97,116]) are more time-consuming than those in which the monodomain formulation is adequate. Mesh size varies dramatically depending on the size of the model and the resolution necessary to capture details relevant to phenomena of interest; this review discusses studies involving models with degrees of freedom (i.e., mesh nodes) ranging from hundreds of thousands [32,33,44,45,[104][105][106][107] to millions [19,[21][22][23][96][97][98] and even tens of millions [95]. At the cell level, ionic models that aim to represent different levels of detail vary considerably in terms of the size of the associated ODE system; for example, the Courtemanche human atrial model has 19 equations [43], the O'Hara human ventricular model has 43 [91], and the Sampson human Purkinje fiber model has 83 [108].…”
Section: Computational Complexity Of Cardiac Electrophysiology Simulamentioning
confidence: 99%